Diversidad de los helechos y plantas afines en el bosque pablo yacu (moyobamba - san martín) - Peláez Peláez, Freddy (2011)
Tropical forests are home to 70 percent of species of flora and fauna of the world, where ferns and related plants are very diverse and abundant, especially in mountainous areas between 1 500 and 2 500 m.a.s.l. San Martín Region ranks third in terms of species richness of ferns and related plants in Peru, with 537 species, but is undergoing a rapid loss of ecosystems, primarily by human actions. PabloYacu is a forest located between 900 and 1650 m.a.s.l., near the city of Moyobamba, with an area of 200 hectares, most of which are forests and there have been about 140 species. In this work, we established 18 plots of 400 m2 (7 200 m2), which were located according to a systematic preferential sampling, recording the species and growth forms (terrestrial, epiphytic, hemiepiphyte, rupicola), cover and abundance . Also recorded UTM coordinates, altitude, temperature and, relative humidity. The richness is in 88 (36 genera and 20 families), with an abundance of 1424 individuals: terrestrial species represent 70.45%, epiphytes are 25.0% and rupícolas 4.55%. The richness and abundance are greater in the plots in the streams, and higher values of coverage are given in plots of the slopes, the presence of rhizomatous species such as Selaginella tarapotensis and Sticherus remotus. A greater abundance is found in creek plots. The Shannon index (H ') is 3.62556, which indicates high diversity. S. tarapotensis and Polybotrya fractiserialis have importance values (IVI) higher to 29,946 and 28,645.